2010
DOI: 10.1107/s1600536810016211
|View full text |Cite
|
Sign up to set email alerts
|

tert-Butyl 4-(2-diazoacetyl)piperazine-1-carboxylate

Abstract: The title crystal structure, C11H18N4O3, is the first diazo­acetamide in which the diazo­acetyl group is attached to an N atom. The piperazine ring is in a chair form and hence the mol­ecule has an extended conformation. Both ring N atoms are bonded in an essentially planar configuration with the sum of the C—N—C angles being 359.8 (2) and 357.7 (2)°. In the crystal structure, the O atom of the diazo­acetyl group accepts two H atoms from C—H donors, thus generating chains of weak hydrogen-bonded R 2 1(7) rings. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The diazoacetamides 3d and 3f crystallised as their ( Z )-rotamers. These data have recently been reported [4243]. …”
Section: Resultssupporting
confidence: 84%
“…The diazoacetamides 3d and 3f crystallised as their ( Z )-rotamers. These data have recently been reported [4243]. …”
Section: Resultssupporting
confidence: 84%
“…The monocarboxylated species in 2 and 3 and the dicarboxylated dianion in 4 have similar chair conformations that correspond to the reported PZ-N-CO 2 R analogues. [42][43][44][45][46][47] The nitrogen atoms in the PZ carboxylated entities reported herein deviate approximately at 0.63 Å in different directions from the mean plane of four cyclic carbon atoms. Both C-O bond lengths are equal and short, and the extreme values are 1.262(1) and 1.274(1) Å; the C-N bond (av.…”
Section: Resultsmentioning
confidence: 74%
“…The deviation of the nitrogen atom from the mean plane formed by the surrounding atoms (carbon and oxygen atoms) is small and characteristic of sp 2 hybridization. 39,[42][43][44][45][46][47] The neutrality of the 1 : 1 acid-base adduct 3 is achieved by the PZH + monocation, while in the 1 : 2 acid-base adduct 4, the neutrality is achieved by two such cations. The In 2, each zwitterion is surrounded by water molecules which mediate interactions between the charged groups of the carboxylated molecule (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This new drug differs from ketamine by a 3-methoxy group in place of the 2-chloro group on the phenyl ring, and an n-ethyl group substituted for the n-methyl group on the amine portion of the molecule (see Fig. 4) [181,182]. Although no formal studies have demonstrated the drug's mechanism of action, methoxetamine is likely to share ketamine's mechanism of action, through N-methyl-D-aspartate (NMDA) receptor antagonism and inhibition of dopamine reuptake.…”
Section: Pharmacology/pharmacokineticsmentioning
confidence: 99%